Are voters rationally ignorant? An empirical study of Portuguese local elections - Silva, Ester Gomes (2006)
The application of the rational choice postulate to a political context invariably leads to the conclusion that most voters are ill informed when making the decision on whom to vote for. In this paper, the authors conduct an empirical evaluation of the rational ignorance theory, based on the model developed by (Rogoff and Sibert Rev Econ Stud LV:1–16, (1988) and by considering that better informed voters reward political candidates who show better performances. The levels of performance are established through the construction of an empirical frontier using the Data Envelopment Analysis (DEA) methodology. According to our results, based on the 1997 Portuguese local elections, even though swing voters do not necessarily behave as rationally ignorant voters, a large majority of voters are rationally ignorant.